A critical assessment of the compressive behavior of reinforced recycled aggregate concrete columns. (15th April 2018) - Xu, Jin-Jun; Chen, Zong-Ping; Ozbakkaloglu, Togay; Zhao, Xin-Yu; Demartino, Cristoforo
Highlights: A fiber section-based nonlinear finite element model was developed to investigate the mechanical behavior of reinforced RRAC columns. Multi-parametric study was performed to investigate the compressive behavior of RRAC columns. A grey correlation analysis was used to evaluate the parametric sensitivity of the compressive behavior of RRAC columns. The results show that the replacement of conventional concrete with RAC affects the overall compressive behavior of RC columns only slightly. The method used for considering the additional water absorption of recycled aggregates has a significant influence on the compressive load capacity of RRAC columns. Abstract: This paper presents a critical assessment of the compressive behavior of reinforced recycled aggregate concrete (RRAC) columns. Previous research has demonstrated that recycled aggregate concrete (RAC), manufactured using crushed concrete aggregates obtained from construction and demolition waste, can be a feasible and environmentally friendly alternative to conventional concrete for the use in structural applications. Currently, very limited information is available in the literature about the methods to be used for designing RC elements manufactured with recycled concrete aggregates. With the aim of extending the available experimental data, a fiber section based nonlinear finite element (FE) model was developed so as to provide in-depth insights into the compressive behavior of RRAC columns. First, a comparison between simulation results of the compressive behavior of RRAC columns and available experimental results were made to validate the FE model. Then, using the validated FE model, a parametric study was performed to investigate the effects of different recycled concrete aggregate (RCA) contents, volumetric ratio and yield strength of longitudinal steel reinforcement, and spacing and yield strength of transverse steel reinforcement on the compressive behavior and load capacity of RRAC columns. Finally, based on the limited available experimental database, a grey correlation analysis was used to evaluate the parametric sensitivity of the compressive behavior of RRAC columns. The experimental and numerical investigations demonstrate that the method used for considering the additional water absorption of RCAs in manufacturing RAC has a significant influence on the compressive load capacity of RRAC columns and that the influence of the RCA content on the compressive load capacity of RRAC columns is lower when compared with other important parameters but this effect should not be ignored in modeling the behavior of RRAC columns.